MODEL SUPERVISI DIGITAL DALAM MENINGKATKAN MUTU PEMBELAJARAN KODING DI SEKOLAH DASAR - Endi Sutrisna; Dethia HS Suci Nurani; Haerul Wafa; Sudaryono Sudaryono (LPPM IAI Dar Aswaja Rokan Hilir, 2026)
Instruction in computer programming (coding) at the elementary school level faces several challenges, including limited teacher competence, lack of ongoing mentoring, and insufficient digital infrastructure. Conventional face-to-face academic supervision is often suboptimal due to low frequency and slow response times. This study aims to design and test a cloud-based digital supervision model to improve the quality of coding instruction in elementary schools. The research employed a research and development (R&D) approach using the ADDIE framework. Participants consisted of 15 fourth and fifth-grade teachers from four public elementary schools in Pandeglang Regency. The instruments included a coding instruction observation sheet, a teacher response questionnaire, and a learning quality assessment rubric. Data analysis techniques comprised descriptive statistics and paired t-tests. The resulting digital supervision model includes the following components: (1) planning through a learning management system (LMS), (2) observation using video recordings and real-time feedback, (3) collaborative reflection in online forums, and (4) rubric-based automated assessment. The trial results showed that the average score of coding instruction quality increased from 66.3 (sufficient category) to 86.8 (good category) after eight weeks of implementing the model (*p* < 0.001). Teacher responses were highly positive, with a mean score of 4.7 out of 5. The digital supervision model proved effective in overcoming geographical and temporal barriers, providing rapid feedback, and fostering collaboration among teachers. Nevertheless, challenges related to digital infrastructure and teachers' ICT literacy need to be anticipated. Digital supervision can serve as an alternative to improve the quality of coding instruction in elementary schools. Technical assistance training and the provision of an integrated platform are strongly recommended.